Wearable device monitoring of HIV health in the face of climate change and weather exposures: protocol for a mixed-methods study - Kassem, Nour; Boutros, Perla; Kwaro, Daniel; Muma, Julius; Obor, David; Munga, Stephen; Maggioni, Martina Anna; Bärnighausen, Till; Winkler, Volker; Barteit, Sandra (BMJ open, 2025)
Introduction Climate change and HIV are interconnected epidemics that increase vulnerability in people living with HIV (PLWH), particularly in sub-Saharan Africa. Despite their public health significance, research on the synergistic effects of these epidemics on the health of PLWH is limited. The advancement of non-invasive wearable technology offers an opportunity to leverage objective health data for large-scale research, addressing this knowledge gap. This study will examine the impact of weather events on distinct health variables of PLWH within the Siaya Health and Demographic Surveillance System (HDSS) in rural Kenya. - Methods and analysis Over a period of 6 months, we continuously monitored health parameters of a total of 200 participants including heart rate, activity and sleep, using consumer-grade wearable devices. We will correlate these health data with real-time weather parameters (ambient temperature, wet bulb globe temperature, precipitation level) from five weather stations within the HDSS area and compare between HIV-positive participants and an HIV-negative control group. Additionally, a convergent mixed-methods approach will explore participants’ perceptions of the impact of weather events on their health and personal experiences. The study aims to inform future research on the complex relationship between HIV and weather events, which are projected to increase in frequency in this region due to climate change and provide valuable insights for policymakers to develop effective measures to protect this vulnerable population amid the growing climate crisis. - Ethics and dissemination This study has been approved by the Research Ethics Committees at Kenya Medical Research Institute, Nairobi (approved on 23 October 2023; SERU 4826) and Heidelberg University Hospital, Germany (approved on 14 February 2023; S-824/2022). Written informed consent was obtained from all participants prior to enrolment, with data anonymised and handled according to Kenyan and German data protection regulations. Research findings will be disseminated through peer-reviewed publications and presented at scientific conferences.